Elevated Lp(a) (Lipoprotein[a]) Levels Increase Risk of 30-Day Major Adverse Cardiovascular Events in Patients Following Carotid Endarterectomy. Issue 10 (October 2020) - Waissi, Farahnaz; Dekker, Mirthe; Timmerman, Nathalie; Hoogeveen, Renate M.; van Bennekom, Joelle; Dzobo, Kim E.; Schnitzler, Johan G.; Pasterkamp, Gerard; Grobbee, Diederick E.; de Borst, Gert J.; Stroes, Erik S.G.; de Kleijn, Dominique P.V.; et al.
Abstract : Background and Purpose: General population studies have shown that elevated Lp(a) (lipoprotein[a]) levels are an emerging risk factor for cardiovascular disease and subsequent cardiovascular events. The role of Lp(a) for the risk of secondary MACE in patients undergoing carotid endarterectomy (CEA) is unknown. Our objective is to assess the association of elevated Lp(a) levels with the risk of secondary MACE in patients undergoing CEA. Methods: Lp(a) concentrations were determined in preoperative blood samples of 944 consecutive patients with CEA included in the Athero-Express Biobank Study. During 3-year follow-up, major adverse cardiovascular events (MACE), consisting of myocardial infarction, stroke, and cardiovascular death, were documented. Results: After 3 years follow-up, Kaplan-Meier cumulative event rates for MACE were 15.4% in patients with high Lp(a) levels (>137 nmol/L; >80th cohort percentile) and 10.2% in patients with low Lp(a) levels (⩽137 nmol/L; ⩽80th cohort percentile; log-rank test: P =0.047). Cox regression analyses adjusted for conventional cardiovascular risk factors revealed a significant association between high Lp(a) levels and 3-year MACE with an adjusted hazard ratio of 1.69 (95% CI, 1.07–2.66). One-third of MACE occurred within 30 days after CEA, with an adjusted hazard ratio for the 30-day risk of MACE of 2.05 (95% CI, 1.01–4.17). Kaplan-Meier curves from time point 30 days to 3 years onward revealed no significant association between high Lp(a) levels and MACE. Lp(a) levels were not associated with histological carotid plaque characteristics. Conclusions: High Lp(a) levels (>137 nmol/L; >80th cohort percentile) are associated with an increased risk of 30-day MACE after CEA. This identifies elevated Lp(a) levels as a new potential risk factor for secondary cardiovascular events in patients after carotid surgery. Future studies are required to investigate whether Lp(a) levels might be useful in guiding treatment algorithms for carotid intervention. Abstract : Supplemental Digital Content is available in the text.